2003
DOI: 10.1103/physrevlett.90.055003
|View full text |Cite
|
Sign up to set email alerts
|

Decharging of Complex Plasmas: First Kinetic Observations

Abstract: The first experiment on the decharging of a complex plasma in microgravity conditions was conducted. After switching off the rf power, in the afterglow plasma, ions and electrons rapidly recombine and leave a cloud of charged microparticles. Because of microgravity, the particles remain suspended in the experimental chamber for a sufficiently long time, allowing precise measurements of the rest particle charge. A simple theoretical model for the decharging is proposed which agrees quite well with the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 18 publications
4
64
0
2
Order By: Relevance
“…As the dustcharging time depends strongly on the electron and ion densities [1], the dust-particle charging time becomes very long in the late plasma afterglow, and the dust-particle charges are considered frozen. It has thus been shown that in the late afterglow of a complex plasma, dust particles indeed keep a residual charge of a few elementary charges and that positively charged, negatively charged, and neutral dust particles coexist for several minutes after the power of the discharge is turned off [9], [10].…”
Section: Dust-cloud Dynamics In a Complexmentioning
confidence: 99%
“…As the dustcharging time depends strongly on the electron and ion densities [1], the dust-particle charging time becomes very long in the late plasma afterglow, and the dust-particle charges are considered frozen. It has thus been shown that in the late afterglow of a complex plasma, dust particles indeed keep a residual charge of a few elementary charges and that positively charged, negatively charged, and neutral dust particles coexist for several minutes after the power of the discharge is turned off [9], [10].…”
Section: Dust-cloud Dynamics In a Complexmentioning
confidence: 99%
“…Consequently, in running discharges, dust particles act as a sink for the electrons of the plasma [2]. The loss of charged species in a complex plasma afterglow is of major importance as it determines the charge carried by the dust particles during the decay process and is fundamental to explain the dust particle residual charges observed experimentally in the late afterglow [12,13]. Dust particle residual charge can be useful (for example, the cleaning of industrial or fusion reactors using electrostatic * lcouedel@physics.usyd.edu.au techniques) or harmful (for example, future single electron devices where residual charge on deposited nanocrystal would be the origin of malfunction).…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, depends on the time scales for plasma loss, electron temperature relaxation, and dust charge fluctuation. A model for the decharging of the dust in a plasma afterglow has been proposed by Ivlev et al 23 to explain the measurements of the residual charge in a microgravity experiment after the discharge was switched off. This model was also compared to measurements of the residual charge in a ground-based experiment by Couëdel et al 24 The conservation of the particle charge after switch off of the plasma was also discussed in connection with a possible microparticle thruster.…”
Section: Discussionmentioning
confidence: 98%